Chapter 6 The Role of Corporate Governance in Macro-Prudential Regulation of Systemic Risk - Dill, Alexander (Practical Finance and Banking Guides, 2019)
Bank Regulation, Risk Management, and Compliance is a concise yet comprehensive treatment of the primary areas of US banking regulation - micro-prudential, macroprudential, financial consumer protection, and AML/CFT regulation - and their associated risk management and compliance systems. The book's focus is the US, but its prolific use of standards published by the Basel Committee on Banking Supervision and frequent comparisons with UK and EU versions of US regulation offer a broad perspective on global bank regulation and expectations for internal governance. The book establishes a conceptual framework that helps readers to understand bank regulators' expectations for the risk management and compliance functions. Informed by the author's experience at a major credit rating agency in helping to design and implement a ratings compliance system, it explains how the banking business model, through credit extension and credit intermediation, creates the principal risks that regulation is designed to mitigate: credit, interest rate, market, and operational risk, and, more broadly, systemic risk. The book covers, in a single volume, the four areas of bank regulation and supervision and the associated regulatory expectations and firms' governance systems. Readers desiring to study the subject in a unified manner have needed to separately consult specialized treatments of their areas of interest, resulting in a fragmented grasp of the subject matter. Banking regulation has a cohesive unity due in large part to national authorities' agreement to follow global standards and to the homogenizing effects of the integrated global financial markets. The book is designed for legal, risk, and compliance banking professionals; students in law, business, and other finance-related graduate programs; and finance professionals generally who want a reference book on bank regulation, risk management, and compliance. It can serve both as a primer for entry-level finance professionals and as a reference guide for seasoned risk and compliance officials, senior management, and regulators and other policymakers. Although the book's focus is bank regulation, its coverage of corporate governance, risk management, compliance, and management of conflicts of interest in financial institutions has broad application in other financial services sectors.